2005
DOI: 10.1111/j.1365-2141.2005.05875.x
|View full text |Cite
|
Sign up to set email alerts
|

The presence of IFNG 3/3 genotype in the recipient associates with increased risk for Epstein–Barr virus reactivation after allogeneic haematopoietic stem cell transplantation

Abstract: Summary Recent studies have shown that interferon‐γ gene (IFNG) polymorphism constitutes a risk factor for acute and chronic graft‐versus‐host disease (GvHD) after allogeneic haematopoietic stem cell transplantation (HSCT). Patients with IFNG 3/3 have been found to be more prone to GvHD. This rather puzzling result, as 3/3 genotype is associated with a decreased IFN‐γ production, was investigated in the present study in the context of Epstein–Barr virus (EBV) reactivation. Microsatellite polymorphism (CA)n wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
2
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 20 publications
0
23
2
1
Order By: Relevance
“…In contrast to published data, 10,11 no significantly increased risk for posttransplantation lymphoma development was apparent in heterozygous or homozygous carriers of the low IFN-producing A allele (HR 1.04, 95% CI 0.59-1.81-2.07, P ϭ .90 for heterozygous AT carriers; and HR 0.81, 95% CI 0.44-1.47, P ϭ .48 for homozygous AA carriers). No significant association of the IFN-␥ polymorphism on survival after lymphoma diagnosis was observed (5-year survival: 44%, 44%, and 49% for AA, AT, and TT allele carriers, respectively; P ϭ .83).…”
Section: Ifn-␥ ؉874a/tcontrasting
confidence: 92%
See 2 more Smart Citations
“…In contrast to published data, 10,11 no significantly increased risk for posttransplantation lymphoma development was apparent in heterozygous or homozygous carriers of the low IFN-producing A allele (HR 1.04, 95% CI 0.59-1.81-2.07, P ϭ .90 for heterozygous AT carriers; and HR 0.81, 95% CI 0.44-1.47, P ϭ .48 for homozygous AA carriers). No significant association of the IFN-␥ polymorphism on survival after lymphoma diagnosis was observed (5-year survival: 44%, 44%, and 49% for AA, AT, and TT allele carriers, respectively; P ϭ .83).…”
Section: Ifn-␥ ؉874a/tcontrasting
confidence: 92%
“…Furthermore, previous studies suggesting an impact of allelic polymorphisms in cytokine genes and HLA on the development of posttransplantation lymphoma could not be confirmed in our study. [10][11][12][13] We made, however, the intriguing observation that polymorphisms in receptors expressed by NK cells were significantly associated with survival after the diagnosis of lymphoma. Homozygous carriers of the high-affinity 158V allele of the FCGR3A (VV patients) showed a significantly improved 5-year survival rate compared with VF and FF patients (Figure 2A-B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, high EBV copy numbers in the blood, suggesting EBV reactivation in recipients of allogeneic hematopoietic stem cell transplantation, were found to be prevalent among patients with a certain IFN-γ genotype. 33 Although previous reports also showed that serum levels of EBV copy numbers may differentiate the clinical features of IM and HLH, 34,35 in our study, we were unable to demonstrate a difference in IFN-γ polymorphisms among patients with IM, HLH and CAEBV. Apart from cytokine gene polymorphisms, Zaitsu et al 36 previously identified a higher prevalence of the QPY haplotype of granzyme B in patients with EBV-HLH than in either patients with IM or healthy controls.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Ncontrasting
confidence: 84%
“…The evaluation of the EBV-specific DNA copies was performed using TaqMan chemistry with detection on Opticon 2 (MJ Research, Waltham, MA, USA) as described previously. 11 Considering that virus-infected cells constitute approximately 1 in 10 4 -10 5 memory B lymphocytes, 12 we assumed the detection threshold for viral reactivation of our method as 10 EBV-DNA copies/10 5 peripheral blood cells.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%